Organoleptic Test and Chemical Characteristics of Klappertaart Products of Manado During Storage - Soputan, Daysie D.; Mamuaja, Christine F.; Lolowang, Tommy F. (Jurnal Ilmu dan Teknologi Pangan, 2016)
Klappertaart cakes are easily to deteriorate, therefore, it is necessary to do a research to analyze the composition of the products related to food safety. The purposes of this study were : 1) to determine the level of consumer preferences to several products of klappertaart in Manado, 2) to analyze the proximate and total microbial content of the most preferable stored klappertaart from organoleptic test results, and 3) to analyze the contents of fatty acids and amino acids of the stored klappertaart. A descriptive method was used in this research. Klappertaart samples were obtained from four leading manufacturers in the city of Manado, and the organoleptic test was done based on the level of preference of 1 - 5 interval, ranging from dislike to very like on taste, flavor/aroma, texture and color. The most preferred products were analyzed the proximate and total microbes in the laboratory of Baristand Manado and profile analysis of amino acids and fatty acids were done at the Integrated Chemical Laboratory of IPB, daily for 3 day storage at the room temperature. The results of the organoleptic test of the 4 klapertaart samples from Manado City indicated that the most preferred sample was A3 with a score of 3.69. The water content of klapertaart from day 1 to day 3 were 63.72% bb, 63.18% bb, and 62.56% bb, respectively. The protein content from day 1 to day 3 were 5.09%, 4.88%, and 4.97%. Fat content of Klappertaart from day 1 to day 3 were 3.00%, 4.08%, and 1.62%. The ash content from day 1 to day 3 were 0.70%, 0.75%, and 0.71%. Carbohydrates calculation using the method by difference from day 1 to day 3 were 27.49, 27.11, and 30.11, respectively. Total microbes in klappertaart of day 1 to day 3 were 1 x 10 3; 3 x 10 3; and 139 x 10 6., respectively. The results of the fatty acid profile test, it obtained 17 fatty acid components and the highest were oleic acid (23.52%, 27.13%, 25.29%), palmitic acid (21.62%, 23.05%, 23.28% ) and lauric acid (9.49%, 10.63%, 10.04%). The results of amino acid test on samples, it was found 15 amino acid components, with the glutamic acid with the highest value of 0.40%, 0.58%, and 0.52%, from day 1 to day 3. This study concluded that the most preferred sample was A3 because of the good tase, not too sweet, not too soft texture and not too sharp flavor, and a high nutritional content during two day storage at the room temperature. It was suggested to carry out further research to determine the mineral contents, and other components as useful nutrition information for consumers. Klappertaart manufacturers in Manado implement a quality assurance system in the development of klappertaart processed products for consumption safety. The Manado City Government should give more attention in terms of training, supervising and support in order for klappertaarts becomeÂ  industrial products that can improve the economy of people of Manado. Keywords: klapertaart, proximate analysis, fatty acids, amino acids, total microbesÂ